2016
DOI: 10.1021/acs.energyfuels.6b00253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Chlorella vulgaris for Bioethanol Production

Abstract: For bioethanol to be a sustainable transportation fuel, appropriate feedstock needs to be established. The focus of the current work is to evaluate if the microalga Chlorella vulgaris could be the feedstock of choice. Exclusive formation of glucose was observed upon the acid (HCl) hydrolysis of C. vulgaris. Microwave irradiation as well as hydrothermal reaction were employed as heating methods. Under optimal hydrolysis conditions using microwave irradiation (100 °C, 1 M HCl, and 10 min), the glucose yield was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…TIB-A01 species was capable of obtaining a sugar concentration of 12 wt% (v/v) and producing an ethanol yield of 0.47 g/g of sugars. Thus, Chlorella microalga was selected because of its capability with high proton efficiency to synthesise and convert a large quantity of carbohydrates into bioethanol production [9].…”
Section: Introductionmentioning
confidence: 99%
“…TIB-A01 species was capable of obtaining a sugar concentration of 12 wt% (v/v) and producing an ethanol yield of 0.47 g/g of sugars. Thus, Chlorella microalga was selected because of its capability with high proton efficiency to synthesise and convert a large quantity of carbohydrates into bioethanol production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Boubabidi et al (2019) reported that the cell immobilization is affected by several factors including physiological state of cells, surface properties and adsorbents, environmental conditions, medium composition, and the pH. Dinesh Kumar et al (2016) investigated the nutrients removal from a shrimp farm wastewater using biofilter filled with a marine microalgae Picochlorum maculatum. The P. maculatum cells have initially been immobilized in round alginate blocks.…”
Section: Immobilized Cellmentioning
confidence: 99%
“…The algal biomass contains high quantities of polysaccharides, which are in the form of starch, sugar, and cellulose. Therefore, algal biomass is considered as a suitable feedstock for bioethanol production …”
Section: Biochemical Conversionmentioning
confidence: 99%
“…Therefore, algal biomass is considered as a suitable feedstock for bioethanol production. 60 Onay 61 cultured microalgae biomass (Hindakia tetrachotoma) using municipal wastewater to study the different saccharification strategies. For microalgae cultivation, 1 L of a flat airlift photo-bioreactor is designed, and the concentration of growth media is varied from 25% to 100% by dilute distilled water.…”
Section: Biochemical Conversionmentioning
confidence: 99%